Poor Nutritional Status and Dynapenia Are Highly Prevalent in Post-Acute COVID-19 - de Blasio, Francesco; Scalfi, Luca; Castellucci, Bianca; Sacco, Anna Maria; Berlingieri, Giulia Miracco; Capitelli, Ludovica; Alicante, Paola; Sanduzzi, Alessandro; Bocchino, Marialuisa (Frontiers in Nutrition, 2022)
Poor nutritional status is a multi-factorial condition that has been associated with hospitalization, the need for intensive care, and mortality in acute Coronavirus disease-2019 (COVID-19) patients. Estimates of malnutrition range between 5 and 69% according to different diagnostic tools in different patient categories. Similarly, with respect to body composition (BC) and muscle function, low values of phase angle (PhA) and handgrip strength (HGS) have been associated with poor disease outcomes. Conversely, only a little evidence is available in post-acute COVID-19 patients. We aimed to combine the evaluation of nutritional status, BC, and muscle strength in a real-life cross-sectional cohort of post-acute COVID-19 patients referred to a rehabilitation center after hospital discharge. This cross-sectional real-life study included 144 post-acute COVID-19 patients (mean age 64.8-yrs; M=95), of which 37% were bedridden (M=60%), referred to a rehabilitation center after hospital discharge. Nutritional status was evaluated with the Mini-Nutritional Assessment (MNA) and Controlling Nutritional status (CONUT) scores. Fat-free mass (FFM), skeletal muscle (SM), and raw variables, i.e. PhA, were estimated with bioelectrical impedance analysis. HGS was measured with a digital handle dynamometer for both dominant and non-dominant body sides. Dynapenia was identified according to the 2019 EWGSOP criteria. With reference to MNA, 18% of patients were malnourished while 62% were at risk of malnutrition. As for CONUT, 21% of cases had moderate-severe malnutrition and 58% light malnutrition. Overall, malnutrition was highly prevalent in older patients with more comorbidities. Marked abnormalities of PhA and HGS were more frequent in bedridden patients or in those malnourished, and when FFM or SM were low. Dynapenic patients were 65% males and 47% females. Malnutrition, BC alterations, and low HGS occur in post-acute COVID-19 patients. Poor nutritional status was more prevalent in bedridden patients. Future studies will help to tailor screening algorithms for full nutritional status assessment to appropriate care processes and rehabilitation strategies.